Pertukaran Sosial Dalam Konteks Dakwah dan Komunikasi - Sarkawi, Sarkawi; Rubino, Rubino; Mailin, Mailin (Innovative: Journal Of Social Science Research, 2025)
Social communication theory gradually continues to develop, all theories introduced by experts have benefits in understanding social dynamics for society. research with the title of the concept of social exchange in the perspective of theory and Islamic perspective aims to find out the relevance of this theory to modern society and to understand the hardness of this theory from an Islamic point of view. The research method used based on the source of the data is a qualitative research method with a descriptive approach by conducting relevant studies based on various sources and relevant literature as well to further study and analyze the concept of this theory based on theoretical perspectives and Islamic concepts. Based on the data collected, the author draws a simple conclusion that this social exchange theory is relevant to current social conditions, especially in the midst of the development of various technologies, because humans are starting to be ignorant and indifferent, although it must be admitted that Islam provides guidance that current social exchanges prioritize the principles of justice, sincerity and broader maslahah